GUNUNG BERAPI DAN PARIWISATA: BERMAIN DENGAN API - Indra Bhaskara, Gde (Jurnal Analisis Pariwisata, 2017)
This research examines and indentifies natural disasters such as volcanic eruptions from the international tourism's context. From the point of view of tourism sector, natural disasters such as volcanic eruptions are addressed by two opposite sides. On the one hand, volcanic eruptions lead to the reluctances and cancellations of potential tourists to visit tourist destinations where those volcanos are located. These cancellations have given immense impacts for those who work in tourism related companies. On the other hand, the eruptions, motivating tourists to come, visit and witness these amazing natural events. There are two methods applied in this research. First method is online desk research and the second one is interview with several stakehiolders who are affected by the eruption of Mount Agung. This research also discusses over some dangers posed by volcanic eruptions to surrounding communities and tourist destination areas.